Intimate partner violence during the COVID-19 pandemic: An online survey - AKVARDAR, YILDIZ (My University, 2023)
Objective:Intimate partner violence (IPV) against women is a human rights violation and a public health concern. The incidence of IPV increases in mass events such as epi-demics. The aim of this study was to assess the nature and the extent of IPV among women in Turkey; to iden-tify the associated factors, and mental health outcomes during the COVID-19 pandemic. Method:The study has a cross-sectional, descriptive design. An online self -report survey, based on World Health Organization guid-ance on epidemiological studies to assess IPV, was con-ducted among women between 09.01.2021 and 09.02.2021. The survey had 69 questions which covered sociodemographic characteristics, relationship history, types of violence and mental well-being. Inclusion crite-ria were being over the age of 18, and having a spouse/partner during the pandemic. Participation was on voluntary basis. 1372 women were included in the analysis. Results:Around a third (30.7%) of participants were exposed to any type of violence before the pan-demic, with most common form being emotional vio-lence, and this rate remained unchanged during the pan-demic, despite the time spent with partners were expect-ed to increase due to isolation measures. 61 women (4.4%), mostly university graduates living in cities, reported being subject to violence for the first time dur-ing the pandemic. 31.2% of them were cases of digital violence. Lower level of education, younger age and partner\"s alcohol and substance use was associated with IPV, and IPV was associated with poorer mental well-being. Discussion:Despite the public health measures taken during the pandemic (e.g. lockdowns), where women would have spent more time isolated with their partners, rates of IPV did not change from pre-pandemic to pandemic. This outcome needs to be compared with findings from other contexts. Strategies to prevent IPV is of utmost importance for the protection of mental well-being of women and the society during and after the pandemic.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; Women`s Health; Sexual Abuse; COVID-19; Domestic Violence; Intimate Partner Violence; DOMESTIC VIOLENCE; HEALTH CONSEQUENCES; WOMEN; PREVALENCE